16. Effect of Watershed Management on Ground Water Potential - Pendke, M.S.; Gore, K.P.; Jeelani Shaikh, A.H. (Journal of Soil and Water Conservation, 2022)
Wagaiwadi watershed of Parbhani district, about 564 hectares was treated in the year 1992-93. Four open wells in treated and two open wells in untreated area of watershed were selected for monitoring ground water table fluctuation to see the effect of watershed management on increase in ground water potential. Meteorological data, viz., rainfall and evaporation were collected. The gravity yield of 2.2 and 1.2 per cent, and monthly change in ground water storage per unit area of 0.22 and 0.19 ha m/ha was calculated for treated and untreated area, respectively. The monthly cumulative ground water potential in both treated and untreated area was calculated. The increase of40 to 45 per cent in accumulated ground water potential due to watershed management practices was observed in treated area after the period of four years.